Core–Shell Ge@Graphene@TiO2 Nanofibers as a High‐Capacity and Cycle‐Stable Anode for Lithium and Sodium Ion Battery. (30th December 2015) - Wang, Xiaoyan; Fan, Ling; Gong, Decai; Zhu, Jian; Zhang, Qingfeng; Lu, Bingan
Abstract : Germanium is considered as a promising anode material because of its comparable lithium and sodium storage capability, but it usually exhibits poor cycling stability due to the large volume variation during lithium or sodium uptake and release processes. In this paper, germanium@graphene nanofibers are first obtained through electrospinning followed by calcination. Then atomic layer deposition is used to fabricate germanium@graphene@TiO2 core–shell nanofibers (Ge@G@TiO2 NFs) as anode materials for lithium and sodium ion batteries (LIBs and SIBs). Graphene and TiO2 can double protect the germanium nanofibers in charge and discharge processes. The Ge@G@TiO2 NFs composite as an anode material is versatile and exhibits enhanced electrochemical performance for LIBs and SIBs. The capacity of the Ge@G@TiO2 NFs composite can be maintained at 1050 mA h g −1 (100th cycle) and 182 mA h g −1 (250th cycle) for LIBs and SIBs, respectively, at a current density of 100 mA g −1, showing high capacity and good cycling stability (much better than that of Ge nanofibers or Ge@G nanofibers). Abstract : Germanium@graphene@TiO2 core–shell nanofibers are synthesized and used as anode materials for lithium ion batteries and sodium ion batteries (LIBs and SIBs). Graphene and TiO2 can double protect the germanium nanofibers in charge and discharge processes. The nanofibers composite as an anode material is versatile and exhibits enhanced electrochemical performance for LIBs and SIBs.